2013
DOI: 10.1371/journal.pone.0072492
|View full text |Cite
|
Sign up to set email alerts
|

SR-BI in Bone Marrow Derived Cells Protects Mice from Diet Induced Coronary Artery Atherosclerosis and Myocardial Infarction

Abstract: SR-BI deficient mice that are also hypomorphic for apolipoprotein E expression develop diet induced occlusive coronary artery atherosclerosis, myocardial infarction and early death. To test the role of SR-BI in bone marrow derived cells, we used bone marrow transplantation to generate SR-BI-null; apoE-hypomorphic mice in which SR-BI expression was restored solely in bone marrow derived cells. SR-BI-null; apoE-hypomorphic mice were transplanted with SR-BI+/+apoE-hypomorphic, or control, autologous SR-BI-null; a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 56 publications
1
26
0
Order By: Relevance
“…This appears to be attributable to deficient expression of this isoform in macrophages and increased macrophage lipoprotein uptake, likely mediated by pinocytosis 74 . This is in contrast to the attenuation of this phenotype upon transplantation of Srb1 expressing bone marrow into the hypomorphic apoE mice 75 , suggesting that SBR1 expression on bone marrow derived cells protects against coronary artery atherosclerosis. This suggests that SRB1 expressed in either macrophages or endothelial cells may contribute in a complex way to the coronary artery lesions.…”
Section: Coronary Artery Atherosclerosismentioning
confidence: 67%
“…This appears to be attributable to deficient expression of this isoform in macrophages and increased macrophage lipoprotein uptake, likely mediated by pinocytosis 74 . This is in contrast to the attenuation of this phenotype upon transplantation of Srb1 expressing bone marrow into the hypomorphic apoE mice 75 , suggesting that SBR1 expression on bone marrow derived cells protects against coronary artery atherosclerosis. This suggests that SRB1 expressed in either macrophages or endothelial cells may contribute in a complex way to the coronary artery lesions.…”
Section: Coronary Artery Atherosclerosismentioning
confidence: 67%
“…SR‐BI/LDLR knockout mice fed a high‐cholesterol diet were more prone to develop atherosclerosis, MI and myocardial fibrosis than LDLR knockout mice fed the same diet (Fuller et al, ; Liao et al, ). SR‐BI knockout/Apo‐E hypomorphic mice showed the same characteristics, but when the animals were transplanted with bone marrow cells that express SR‐BI, the monocyte recruitment was attenuated, levels of IL‐6 were lower in plasma and the animals showed less atherosclerosis, MI, and cardiac fibrosis (Pei et al, ). Pagler et al () showed that SR‐BI is a mediator to the retroendocytosis of HDL and LDL, and the resecretion of HDL particle contributes to cholesterol efflux.…”
Section: Discussionmentioning
confidence: 99%
“…We have previously demonstrated that monocyte recruitment into atherosclerotic plaques is attenuated by restoration of SR-BI expression in the bone marrow of SR-BI knockout/apoE hypomorphic mice, and that SR-BI-deficient monocytes bind VCAM-1 and ICAM-1 more readily than SR-BI-expressing monocytes. 29 Monocytes can be divided into subsets based on their level of Ly6C expression. Ly6C hi monocytes are considered to be more inflammatory, adhere more efficiently to activated endothelium, migrate more efficiently into established atherosclerotic plaques, and selectively accumulate in atherosclerotic plaques compared with Ly6C lo monocytes.…”
Section: Fuller Et Al Coronary Atherosclerosis In Sr-bi/ldlr Dko Micementioning
confidence: 99%